2020
DOI: 10.1177/0886260519897327
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cold Case Homicide Survivors’ Perceptions of and Relationships With Law Enforcement

Abstract: Given the nature of unsolved homicide, a complicated dynamic exists between survivors of cold case homicides and law enforcement personnel. The current study utilizes interviews with 24 survivors to explore the perceptions associated with this relationship. Employing a grounded theory framework, we find several themes depicted within these narratives that guide survivors’ overall perceptions of their relationship with law enforcement, including investigative and communication efforts. Results indicate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This notion of improved relationships and communication with residents, is an important avenue for homicide detectives as well during the homicide investigation. Family members of homicide victims (i.e., homicide survivors) reported a positive relationship with and trust in police when they felt listened to and had open communication with the homicide detective on their case (Wellman & Meitl, 2020). Unsolved cases leaves survivors to feel that their loved one has been forgotten or overlooked and leaves : 2007-2008 many feeling dissatisfied with the justice system (Stretesky et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This notion of improved relationships and communication with residents, is an important avenue for homicide detectives as well during the homicide investigation. Family members of homicide victims (i.e., homicide survivors) reported a positive relationship with and trust in police when they felt listened to and had open communication with the homicide detective on their case (Wellman & Meitl, 2020). Unsolved cases leaves survivors to feel that their loved one has been forgotten or overlooked and leaves : 2007-2008 many feeling dissatisfied with the justice system (Stretesky et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Unsolved cases leaves survivors to feel that their loved one has been forgotten or overlooked and leaves : 2007-2008 many feeling dissatisfied with the justice system (Stretesky et al, 2010). Community-wide forums where homicide detectives, homicide survivors, and other important parties come together to discuss the cases, may help family members feel heard, respected, and their family member remembered; which may be as important as solving the case (Wellman & Meitl, 2020;Stretesky et al, 2016). Beyond the importance of the relationship between the police and residents may be the historical context of the neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very recent study showed that 24 survivors of cold cases (i.e. relatives of the deceased) perceived detectives of the initial and follow-up investigations as rather incompetent or ineffective (Wellman and Meitl, 2020). Although this study looked at cold cases in the USA, we can assume that similar feelings are harboured by Dutch survivors, which would reflect unfavourably on Dutch Criminal Investigation Department detectives.…”
mentioning
confidence: 81%